Akidah dan Eskatologi dalam Studi Hadis Tematik: Padang Mahsyar dan Syafaat Nabi Muhammad SAW - Salamah Rahayu; Muhamad Abubakar Sidiq; Repa hudan; Muhammad alif (IHSANIKA : Jurnal Pendidikan Agama Islam, 2025)
This study explores the theological and eschatological dimensions of Islam through a thematic approach to hadith, focusing particularly on the events of the Day of Gathering (Padang Mahsyar) and the intercession (shafa‘ah) of Prophet Muhammad (peace be upon him). In Islamic eschatology, Padang Mahsyar represents a critical stage that manifests divine justice in its absolute form, where every individual is gathered and held accountable for their deeds. The Prophet's intercession is a central concept reflecting God’s mercy, conveyed through the Messenger, especially for those who uphold the oneness of God (tawhid). This research employs a qualitative method based on library research, using thematic analysis of hadiths from major sources such as Sahih al-Bukhari and Sahih Muslim. The findings suggest that a deeper understanding of Padang Mahsyar and the Prophet’s intercession can reinforce the faith ('aqidah) of Muslims while enhancing their moral awareness and piety in daily life.